Metal–Ligand Core–Shell Nanocomposite Catalysts for the Selective Semihydrogenation of Alkynes1. Issue 5 (13th December 2012) - Mitsudome, Takato; Takahashi, Yusuke; Ichikawa, Satoshi; Mizugaki, Tomoo; Jitsukawa, Koichiro; Kaneda, Kiyotomi
<x xml:space="preserve">Abstract</x> Catalysts with a sheltered upbringing: Novel core–shell nanocomposite catalysts consisting of active metal nanoparticles encapsulated by macroligands have been prepared. They have Pd nanoparticles (PdNPs) as an active core and shell ligands having sulfoxide moieties coordinated to the PdNPs. The shell protects the catalyst from coordination by alkenes and allows the lead‐free selective semihydrogenation of a wide range of alkynes without any additives (see scheme).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>